Determining of university desertion: survival analysis - Núñez-Naranjo, Aracelly (2022)
University desertion is the subject of analysis by several authors over the years. The different causes for which a student abandons his studies and the ways to reduce it, entail the interest of the study. The research was positive with a quantitative approach. The data collection was carried out through a survey, and an observation sheet to the student’s files, we proceeded with the analysis of the Kaplan Meier survival curve, on a base made up of 1078 undergraduate students enrolled in the first semester. in 2014 with follow-up to 2019. It is concluded that the existing university dropout factors are personal and social. The incident variables are age, gender, marital status, region, school, family, venue, modality, homologation, and career. There are no significant differences in ethnicity, school, age and quintile, averages.